Genetic parameter estimates in irrigated barley genotypes in the brazilian savanna of the Federal District - Thomé, Rodolfo Dias (2024)
Barley is an important crop for Brazil and an advantageous alternative for irrigated cultivation in the Brazilian Savanna. The present study aimed to characterize and estimate genetic, phenotypic, and environmental parameters and select genotypes from the Embrapa Cerrados irrigated barley working collection. The experiment was established in Randomized Blocks with four replications under irrigation in Embrapa Cerrados, Planaltina-DF. The traits evaluated were grain yield, commercial classification of first grains, 1000-seed weight, plant height, lodging, and cycle. The genetic parameters and correlations between the traits evaluated were obtained. High values of heritability, in a broad sense, were verified. The high coefficients of genotypic variance and the high selective accuracy obtained corroborate the favorable environmental condition for the selection of genotypes. It was verified that the genotypic correlations were higher than the phenotypic correlation coefficients, showing a greater contribution of genetic factors in the expression of the traits. Earlier genotypes had higher grain yields, first-class commercial classification, 1000-seed weight, and height. There was a strong positive correlation between the commercial classification of first grains and 1000-seed weight. Genotypes PFC 2005143, PFC 2006134, and PFC 2004212 were selected for use in crossbreeding blocks within the Brazilian irrigated barley breeding program.